Effect of alirocumab on coronary atheroma volume in Japanese patients with acute coronary syndromes and hypercholesterolemia not adequately controlled with statins: ODYSSEY J-IVUS rationale and design. Issue 6 (June 2018) - Ako, Junya; Hibi, Kiyoshi; Kozuma, Ken; Miyauchi, Katsumi; Morino, Yoshihiro; Shinke, Toshiro; Tsujita, Kenichi; Uno, Kiyoko; Kawabata, Yumiko; Hiro, Takafumi
Highlights: ODYSSEY J-IVUS is a phase IV study in adults with an acute coronary syndrome and hypercholesterolemia. Patients will be randomized to alirocumab or standard-of-care, both with a statin. The primary objective is the effect of alirocumab on coronary atheroma progression. Abstract: Background: Serial intravascular ultrasound (IVUS) imaging can be used to evaluate the effect of cholesterol-lowering on coronary atheroma progression and plaque volume, with evidence of potential incremental effects with more aggressive lipid-lowering treatments. Alirocumab is a highly specific, fully human monoclonal antibody to proprotein convertase subtilisin/kexin type 9 (PCSK9). This study will investigate the effect of alirocumab on coronary artery plaque volume in Japanese patients with a recent acute coronary syndrome (ACS) and hypercholesterolemia while on stable statin therapy. Methods: ODYSSEY J-IVUS is a phase IV, open-label, randomized, blinded IVUS analysis, parallel-group, multicenter study in Japanese adults recently hospitalized for an ACS and who have elevated low-density lipoprotein cholesterol (LDL-C) values [≥100 mg/dL (2.6 mmol/L)] at ACS diagnosis and suboptimal LDL-C control on stable statin therapy. Patients will be randomized (1:1) to receive alirocumab or standard-of-care (SOC). The alirocumab arm will receive alirocumab 75 mg every 2 weeks (Q2W) added to statin therapy (atorvastatin ≥10 mg/day or rosuvastatin ≥5 mg/day), with a dose increase to 150 mg Q2W in patients whose LDL-C value remains ≥100 mg/dL at week 12. The SOC arm will receive atorvastatin ≥10 mg/day or rosuvastatin ≥5 mg/day, with dose adjustment to achieve LDL-C <100 mg/dL. Post-treatment IVUS imaging will be done at week 36 ± 2. The primary objective is to compare the effect of alirocumab versus SOC on coronary atheroma progression (percent change in normalized total atheroma volume) after 9 months of treatment. Conclusion: ODYSSEY J-IVUS will provide insights into the effect of alirocumab on coronary atherosclerotic plaque volume in patients with a recent ACS and hypercholesterolemia while on stable statin therapy. ClinicalTrials.gov number :NCT02984982 .